Glass fiber reinforced PBT (Polybutylene Terephthalate) material as well as preparation method and application thereof

By using the compound of general formula (I) as a hydrolyzing agent in PBT materials, the problems of poor hydrolysis under high temperature and high humidity conditions and severe mold scale during injection molding are solved, and the effect of improving hydrolysis resistance and reducing mold scale generation is achieved.

CN119708626AActive Publication Date: 2025-03-28SHANGHAI KINGFA SCI & TECH +1

Patent Information

Application Number
CN202411963105.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing PBT materials are easily hydrolyzed under high temperature and high humidity conditions, resulting in a decrease in mechanical strength and easily produce mold scale during injection molding, affecting production efficiency.

Method used

The compound of general formula (I) is used as a hydrolyzing agent, and the amide group reacts with the end carboxylic group of PBT to block the end carboxylic group to reduce the hydrolysis of the material, and absorbs oligomers or small molecule substances in the system through the hydrolyzing agent to reduce the generation of mold scale.

Benefits of technology

It improves the hydrolysis resistance of PBT materials, reduces the generation of mold scale during injection molding, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217664780000021
    Figure BDA0005217664780000021
  • Figure BDA0005217664780000041
    Figure BDA0005217664780000041
  • Figure BDA0005217664780000051
    Figure BDA0005217664780000051
Patent Text Reader

Abstract

The invention belongs to PBT (polybutylene terephthalate) materials, and particularly discloses a glass fiber reinforced PBT material as well as a preparation method and application thereof. According to the glass fiber reinforced PBT material, in the injection molding process, the hydrolysis resistance of PBT is improved, meanwhile, the hydrolysis-resistant agent can absorb oligomers or small molecular substances generated by PBT or auxiliaries, the content of the oligomers and the small molecular substances in a system is reduced, and the problem of mold scale generated in the injection molding process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to PBT materials, and specifically relates to a glass fiber reinforced PBT material and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a polyester made by polycondensation of terephthalic acid and 1,4-butanediol. PBT has good mechanical properties, thermal stability, and easy molding, and is widely used in the fields of automobiles, electronic appliances, etc. In order to increase the comprehensive performance of PBT materials, PBT materials will also add some antioxidants, flame retardants, lubricants and other additives. At the same time, because PBT generally has the defect of large shrinkage after molding, the industry generally improves the shrinkage and strength by adding fillers such as glass fiber. Such materials are generally called reinforced PBT materials. Conventional PBT materials or reinforced PBT materials have ester bonds in PBT itself, which are easily hydrolyzed under high temperature and high humidity conditions, resulting in ester bond breakage. In this process, the self-catalytic effect of the end carboxyl group of PBT will accelerate the degradation of PBT, resulting in a significant reduction in the mechanical strength of the material and affecting the normal use of the material. Therefore, it is generally necessary to add some hydrolysis resistance agents to improve the hydrolysis resistance of the material.

[0003] PBT has a fast crystallization rate, so it is generally formed by injection molding. However, the high temperature during the injection molding process not only accelerates the hydrolysis process of PBT to a certain extent, but also causes PBT or conventional hydrolysis-resistant agents to decompose more oligomers and small molecules. This phenomenon will make it easier for the material to have more residues on the mold during the injection molding process, forming serious mold scale. During the continuous processing process, the mold scale on the mold surface needs to be cleaned regularly, resulting in low production efficiency.

[0004] Therefore, there is still a need to continue to develop a reinforced PBT material that is resistant to hydrolysis and has low mold fouling. Summary of the invention

[0005] In view of the problems of poor hydrolysis resistance of PBT materials involved in the above-mentioned prior art and serious mold deposit phenomenon during the injection molding process, the present invention will provide a glass fiber reinforced PBT material and a preparation method and application thereof.

[0006] To achieve the above purpose, the following technical solutions are specifically included:

[0007] In one aspect, the present invention provides a use of a compound of formula (I) as a hydrolysis resistance agent in a glass fiber reinforced PBT material, wherein the compound of formula (I) is as follows:

[0008]

[0009] Among them, X1, X2, X3, X4, and X5 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.

[0010] In the process of injection molding of the glass fiber reinforced PBT material of the present invention, the compound of general formula (I) belongs to an amide compound. As the anti-hydrolysis agent in the glass fiber reinforced PBT material, the amide group of the anti-hydrolysis agent is easy to react with the terminal carboxyl group of PBT to achieve the end-capping of the terminal carboxyl group of PBT, and consume the terminal carboxyl group in the material. Therefore, the present invention improves the hydrolysis resistance of PBT by reducing the proportion of the terminal carboxyl group of the material. At the same time, the anti-hydrolysis agent can absorb the oligomers or small molecules generated by PBT or the auxiliary agent, reduce the content of oligomers and small molecules in the system, and improve the mold scale problem generated in the injection molding process.

[0011] Preferably, the compound of general formula (I) includes at least one of acrylamide, p-methylcinnamamide, trans-2,5-dimethoxycinnamamide and 4-chlorocinnamamide.

[0012] A glass fiber reinforced PBT material comprises the following raw material components in parts by weight:

[0013] PBT resin 59-91 parts, glass fiber 14-32 parts, the anti-hydrolysis agent 0.7-2.6 parts, auxiliary agent 0.1-2 parts.

[0014] Preferably, the glass fiber reinforced PBT material comprises the following raw material components in parts by weight: 60-90 parts of PBT resin, 15-30 parts of glass fiber, 1-2.5 parts of anti-hydrolysis agent, and 0.5-1.6 parts of auxiliary agent.

[0015] Preferably, the mass percentage of PBT resin in the glass fiber reinforced PBT material is not less than 50%, preferably not less than 60%, and more preferably not less than 70%.

[0016] Preferably, the intrinsic viscosity of the PBT resin is 0.6-1dL / g, more preferably 0.7-0.8dL / g. The intrinsic viscosity of the PBT resin can be 0.6, 0.7, 0.8, 0.9, 1.0dL / g, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range. The intrinsic viscosity of the PBT resin of the present invention is the intrinsic viscosity at 25°C tested by the GB / T 14190-2017 method. Under the above-mentioned intrinsic viscosity of the PBT resin, the glass fiber reinforced PBT material can maintain low mold deposit quality and high hydrolysis resistance during the injection molding process.

[0017] Preferably, the glass fibers are chopped glass fibers.

[0018] Preferably, the average diameter of the glass fiber is 10-13 μm, and the diameter of the glass fiber can be 10, 11, 12, 13 μm, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0019] The present invention can measure the diameter of the glass fiber by means of a scanning electron microscope.

[0020] Preferably, the mass percentage of the glass fiber in the glass fiber reinforced PBT material is 15-30%, specifically 15%, 17%, 19%, 21%, 23%, 25%, 27%, 29%, 30%, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0021] At the above-mentioned glass fiber content, not only can the reinforcing effect of the glass fiber be maximized, but the hydrolysis resistance of the material can also be improved.

[0022] Preferably, the mass percentage of the anti-hydrolysis agent in the glass fiber reinforced PBT material is 1-2.5%, and further preferably, the mass percentage of the anti-hydrolysis agent in the glass fiber reinforced PBT material is 1.5-2%, specifically 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0023] Preferably, the auxiliary agent includes an antioxidant and a lubricant.

[0024] Further preferably, the antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis(3-laurylthiopropionate), and tris[2.4-di-tert-butylphenyl]phosphite; and the lubricant includes at least one of ethylene bisstearamide, E wax, calcium stearate, and pentaerythritol tetrastearate.

[0025] The preparation method of the glass fiber reinforced PBT material of the present invention comprises the following steps: mixing PBT resin, hydrolysis resistance agent, auxiliary agent and glass fiber, melting them under light, and then extruding and granulating to obtain the glass fiber reinforced PBT material.

[0026] In the preparation of glass fiber reinforced PBT material, the present invention prepares the glass fiber reinforced PBT material by melting under light, which can improve the hydrolysis resistance of the material; on the other hand, the carbon-carbon double bonds in the acrylamide group of the hydrolysis-resistant agent polymerize themselves to form a four-membered carbon ring macromolecule, which increases its molecular weight and is more difficult to precipitate during the injection molding process, thereby avoiding the precipitation of the hydrolysis-resistant agent to aggravate the mold scale problem.

[0027] Preferably, the melting temperature is 200-240° C., and the wavelength of the light is 250-320 nm.

[0028] The present invention also provides an application of a glass fiber reinforced PBT material in the preparation of electronic appliances, in particular, in the preparation of connectors and controllers in the electronic appliance industry.

[0029] Compared with the prior art, the present invention has the following beneficial effects: the glass fiber reinforced PBT material of the present invention improves the hydrolysis resistance of PBT during the injection molding process, and the anti-hydrolysis agent can absorb the oligomers or small molecules produced by PBT or additives, reduce the content of oligomers and small molecules in the system, and improve the mold deposit problem produced during the injection molding process. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The components and raw materials used in the examples and comparative examples of the present invention are the same unless otherwise specified.

[0031] PBT resin 1: PBT GX110, intrinsic viscosity: 0.6dL / g, Yizheng Chemical Fiber;

[0032] PBT resin 2: PBT GX111, intrinsic viscosity: 0.7dL / g, Yizheng Chemical Fiber;

[0033] PBT resin 3: PBT GX121, intrinsic viscosity: 1.0 dL / g, Yizheng Chemical Fiber;

[0034] The chemical structural formula of the hydrolysis resistance agent is shown in the following formula I:

[0035]

[0036] Among them, X1, X2, X3, X4, and X5 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.

[0037] Hydrolysis-resistant agent 1: acrylamide, Hefei Tianjian Chemical Co., Ltd.;

[0038] Hydrolysis resistance agent 2: p-Methylcinnamamide, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] Hydrolysis resistant agent 3: trans-2,5-dimethoxycinnamic acid amide, Sigma-Aldrich;

[0040] Hydrolysis resistance agent 4: 4-chlorocinnamamide, Shanghai Huayuan Century Trading Co., Ltd.;

[0041] Small molecule capture agent: 3-phenyl-2-acrylic acid, Shanghai Jizhi Biochemical Technology Co., Ltd.;

[0042] Glass fiber 1: 10 μm in diameter, ECS10-4.5-534AKF, Jushi glass fiber;

[0043] Glass fiber 2: diameter 11 μm, ECS11-4.5-534A, Jushi glass fiber;

[0044] Glass fiber 3: diameter 13 μm, ECS13-4.5-534A, Jushi glass fiber;

[0045] Antioxidant 1: SONOX 1010, Shandong Sanfeng;

[0046] Antioxidant 2: RIANOX 412S, Tianjin Li’anlong;

[0047] Lubricant: PETS-AP, hair base.

[0048] Examples 1-15 and Comparative Examples 1-5

[0049] A method for preparing a glass fiber reinforced PBT material comprises the following steps:

[0050] (1) According to the formula in Table 1-2, weigh PBT resin, antioxidant, lubricant, and hydrolysis resistance agent respectively, mix them evenly, and then add them to the extruder;

[0051] (2) According to the formula in Table 1-2, glass fiber is added to the extruder from the side feed, fully melted and mixed evenly, the melting temperature is 200-240°C, and light with a wavelength of 280nm is applied to the homogenization section of the extruder, extruded and granulated to obtain glass fiber reinforced PBT material.

[0052] Table 1

[0053]

[0054]

[0055] Table 2

[0056]

[0057] The glass fiber reinforced PBT materials prepared in the above examples and comparative examples were subjected to injection mold fouling test and rapid molding effect test:

[0058] (1) Injection mold deposit test: Place a metal steel sheet at the mold exhaust port, and continuously inject 200 times at 260°C. Collect the mold deposit on the metal sheet and weigh it. The mass difference between the front and back of the metal sheet is used to characterize the size of the mold deposit. The smaller the mass difference, the less mold deposit.

[0059] (2) Hydrolysis resistance: The evaluation material is made into corresponding ISO standard specimens. After being stored in a hot and humid environment of 85°C and 85% RH for 500 h, the retention rate of tensile strength and notched impact strength of the specimens after the test is evaluated compared with the specimens before the test. The tensile strength is tested according to the specimen of ISO 527 1A-2019 at a test speed of 5 mm / min; the notched impact strength is tested according to the specimen of ISO 179 / 1eA at a pendulum of 4J. The greater the retention rate of tensile strength and notched impact strength, the better the hydrolysis resistance.

[0060] The above test results are shown in Table 3.

[0061] Table 3

[0062]

[0063]

[0064] It can be seen from Example 1 and Comparative Example 1 that the present invention adds an anti-hydrolysis agent in the preparation of glass fiber reinforced PBT material, which helps to improve the hydrolysis resistance of the material. At the same time, the anti-hydrolysis agent with a macromolecular structure captures small molecules in the system during the injection molding process, reduces the generation of mold deposits, and the anti-hydrolysis agent with a macromolecular structure is not easy to precipitate, unlike the existing conventional anti-hydrolysis agent which will further aggravate the mold deposits.

[0065] It can be seen from Examples 1-3 that the content of small molecular substances in PBT resins of different intrinsic viscosities is different. It can be seen from the examples that as the intrinsic viscosity of the PBT resin in Examples 2, 1, and 3 increases, the mold deposit quality gradually decreases, the retention rate of tensile strength and notched impact strength increases slightly, and the hydrolysis resistance increases slightly. Therefore, considering comprehensively, the intrinsic viscosity of the PBT resin can be selected to be 0.6-1L / g, at which time the glass fiber reinforced PBT material maintains a lower mold deposit quality and a higher hydrolysis resistance during the injection molding process.

[0066] It can be seen from Examples 1, 4-5 and Comparative Example 3 that as the content of glass fiber in the system increases in Examples 4, 5, 1 and Comparative Example 3, the hydrolysis resistance first increases and then decreases. The content of glass fiber should not be too much, otherwise due to the excessive glass fiber content, the shear is large and the compatibility of glass fiber and matrix is ​​poor, which leads to an increase in the mold scale content of small molecular substances and a deterioration of hydrolysis resistance. In the system of the present invention, the mass percentage of glass fiber in the glass fiber reinforced PBT material is 15-30%, which can maintain a low mold scale mass and a high hydrolysis resistance.

[0067] It can be seen from Examples 1 and 6-7 that, with the increase in the diameter of the glass fiber, the mold deposit quality and hydrolysis resistance in the system of the present invention remain substantially unchanged.

[0068] It can be seen from Examples 1, 11-13 and Comparative Example 2 that as the content of the anti-hydrolysis agent in Examples 11, 1, 12, 13 and Comparative Example 2 increases, the mold scale quality first decreases and then increases, and the tensile strength and notched impact strength retention rates remain basically unchanged; when the anti-hydrolysis agent content is low, it is unable to fully capture the free PBT small molecules, resulting in low mold scale and tensile strength and notched impact strength retention rates, and when the capture agent content is too high, the anti-hydrolysis agent is in excess, and the excess anti-hydrolysis agent, as a small molecule substance that produces mold scale, increases the mold scale quality, resulting in an increase in mold scale. Therefore, in the system of the present invention, when the mass percentage of the anti-hydrolysis agent in the glass fiber reinforced PBT material is 1-2.5%, a low mold scale quality and a high hydrolysis resistance can be maintained.

[0069] It can be seen from Examples 1 and 8-10 that, at the same weight, all types of anti-hydrolysis agents containing amide groups can maintain low mold deposit quality and high hydrolysis resistance. At the same time, in Comparative Example 5, 3-phenyl-2-acrylic acid containing carboxylic acid groups is used. Compared with the case of no anti-hydrolysis agent in Comparative Example 1, although the mold deposit quality is reduced to a certain extent in Comparative Example 5, the hydrolysis resistance of the material cannot be significantly improved. Therefore, the present invention uses an anti-hydrolysis agent containing amide groups to achieve both low mold deposit quality and high hydrolysis resistance.

[0070] It can be seen from Examples 1 and 14-15 that due to the different contents of the additive and PBT, the content of small molecules produced by degradation during the processing is different. When the content of the additive is high, it itself, as a small molecule substance, will cause high mold deposits. Therefore, when the components of the glass fiber reinforced PBT material are within the weight parts required by the present invention, the glass fiber reinforced PBT material can maintain a lower mold deposit quality and a higher hydrolysis resistance during the injection molding process.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. Use of a compound of general formula (I) as a hydrolysis resistance agent in glass fiber reinforced PBT material, characterized in that: The compound of general formula (I) is shown below: Among them, X1, X2, X3, X4, and X5 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.

2. The use according to claim 1, characterized in that The compound of general formula (I) includes at least one of phenylacrylamide, p-methylcinnamamide, trans-2,5-dimethoxycinnamamide and 4-chlorocinnamamide.

3. A glass fiber reinforced PBT material, characterized in that: The invention comprises the following raw material components in parts by weight: 59-91 parts of PBT resin, 14-32 parts of glass fiber, 0.7-2.6 parts of the anti-hydrolysis agent according to claim 1 or 2, and 0.1-2 parts of an auxiliary agent.

4. The glass fiber reinforced PBT material according to claim 3, characterized in that: Include at least one of the following: A. The intrinsic viscosity of the PBT resin is 0.6-1dL / g; B. The diameter of the glass fiber is 10-13 μm.

5. The glass fiber reinforced PBT material according to claim 3, characterized in that: The mass percentage of the anti-hydrolysis agent in the glass fiber reinforced PBT material is 1-2.5%.

6. The glass fiber reinforced PBT material according to claim 3, characterized in that: The mass percentage of the glass fiber in the glass fiber reinforced PBT material is 15-30%.

7. The glass fiber reinforced PBT material according to claim 3, characterized in that: The auxiliary agents include antioxidants and lubricants.

8. A method for preparing the glass fiber reinforced PBT material according to any one of claims 3 to 7, characterized in that: The steps include: The PBT resin, the hydrolysis resistant agent, the auxiliary agent and the glass fiber are mixed, melted under light, and then extruded and granulated to obtain the glass fiber reinforced PBT material.

9. The method for preparing the glass fiber reinforced PBT material according to claim 8, characterized in that: The wavelength of the light is 250-320nm.

10. Use of the glass fiber reinforced PBT material according to any one of claims 3 to 7 in the preparation of electronic appliances.

Citation Information

Patent Citations

  • Low-mold-scale flame-retardant reinforced PBT composite material as well as preparation method and application thereof

    CN112745642A

  • Thermoplastic resin composition, method for preparing the same, and molded article

    CN116096813A

  • Polyester composition as well as preparation method and application thereof

    CN118530563A

  • FIRE RETARDANT COMPOSITION OF ECO-FRIENDLY FLOORING MATERIAL COMPRISING OF WATER SOLUBLE n-CYANIC ACID ESTER POLYMER RESIN AND HYBRID DIVIDED COMPLEX

    KR102566033B1

  • Halogen-free flame-retardant-reinforced polyester composite material having high hydrolysis resistance

    WO2024250653A1

Cited By

  • Preparation method and application of linear chain modified hyperbranched polyester and polybutylene terephthalate composite material

    CN122587176A